Growth patterns and morphometric analysis of marketable Strombus spp. from Batam, Indonesia - INSANIAH RAHIMAH; DIETRIECH G. BENGEN; ETTY RIANI; WINDARTI WINDARTI; I WAYAN NURJAYA; SITI MAHMUDA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rahimah I, Bengen DG, Riani E, Windarti, Nurjaya IW, Mahmuda S. 2025. Growth patterns and morphometric analysis of marketable Strombus spp. from Batam, Indonesia. Biodiversitas 26: 4618-4627. This study investigates morphometric variations and growth patterns of three commercially valuable Strombus species from Batam, Indonesia: Laevistrombus canarium, Laevistrombus turturella, and Strombus canarium. A total of 1.786 specimens were collected from Rempang, Galang, and Panjang Islands. Nine morphometric parameters were measured, including Shell Width (SW), Shell Length (SL), Lip Thickness (LT), and Whorl Amount (WA). Statistical analyses, including Principal Component Analysis (PCA) and Pearson correlation, revealed significant interspecific differences, with SW, LT, and WA emerging as the most discriminant traits. L. canarium and L. turturella showed partial morphological overlap, whereas S. canarium exhibited distinct features. Correlation analysis indicated strong positive relationships among SW, BWL, and AL, with L. canarium and L. turturella showing stronger size-related relationships (R² = 0.63) than S. canarium (R² = 0.47). Growth analysis confirmed hypoallometric patterns across all species, with b-values of 2.47, 2.65, and 2.20, respectively. Morphological variation was shaped by both intrinsic factors (life stage, gonadal maturity) and extrinsic factors (substrate type, food availability). These findings highlight species-specific adaptations to local benthic habitats and underscore the value of morphometric traits as ecological indicators, underscoring the unique ecological niches of the studied species and their importance for biodiversity conservation. By linking shell morphology to environmental conditions, this study provides a practical basis for monitoring ecosystem health, informing adaptive strategies for sustainable fisheries management and biodiversity conservation in the Indo-Pacific region.